The Historical Value of Cooperatives in Improving Economic Welfare and Its Implementation in the As Sakinah Kamal Bangkalan Islamic Financial Services Cooperative (KJKS) - Natasya Dwi Yanti; Mustafida; Mashudi (HISTORICAL: Journal of History and Social Sciences, 2025)
Cooperatives have long been an important part of the Indonesian people's economy, since their emergence in the late 19th century, cooperatives have developed into a forum for the community to improve economic welfare through the principles of togetherness and mutual cooperation. Along with economic development and more complex financial needs, the concept of cooperatives has experienced innovation with the presence of Sharia Financial Services Cooperatives (KJKS). KJKS is a form of cooperative that operates according to Shari'ah principles, avoiding usury and using Shari'ah contracts in its operations. KJKS has successfully provided fair and Sharia-compliant financial services in various regions, including Kamal, Bangkalan. This success is characterized by increased access to finance for the community and microeconomic growth in the region. This research examines the history of Indonesian cooperatives, the legal basis and basic principles of KJKS, and its application in Kamal. It is hoped that the results of this research will provide insight into the role of KJKS in community economic empowerment and its contribution to the Shari'a-based financial system in Indonesia, including policy recommendations for program optimization.